Paleoenvironment of the Miocene Lemau Formation Based on the Palynology Analysis in Seluma, Bengkulu - Sakilla Gia Mentari; Winantris Winantris; Lia Jurnaliah (Jambura Geoscience Review, 2023)
The Lemau Formation is a rock formation that forms the Bengkulu Basin in the Bengkulu Strip. The rocks in this formation contain hydrocarbon reserves in the form of coal. There has yet to be any research on the palynomorphs in the coal-bearing rocks in this formation. Palynomorph analysis was performed on nine samples from the P.T. Bara Indah Lestari, Seluma. The study aims to reconstruct the paleoenvironment and age of the coal-bearing rocks. The sampling technique uses stratigraphic measurements and hydrogen peroxide preparation. There were four changes in the depositional environment, namely the deposition of BIL 10-BIL 11 in the form of a freshwater peat swamp environment and BIL 12 in the form of a mangrove environment in the Early Miocene marked by the presence of Florschuetzia levipoli. The environment changed to a lagoon, indicated by the presence of foraminifera lining test and dinocyst in the deposition of BIL 13-BIL 15 samples in the Middle Miocene with a marked presence of Alnipollenites verus. The environment changed again during the deposition of BIL 16-BIL 18 to become a mangrove environment in the Middle Miocene. Overall, the paleoenvironment of the Lemau Formation is a freshwater peat swamp to a lagoon. Environmental changes are possible due to tectonic activity and climate change.